Pretreatment HIV drug resistance among adults initiating ART in Namibia. (20th August 2018) - Taffa, Negussie; Roscoe, Clay; Sawadogo, Souleymane; De Klerk, Michael; Baughman, Andrew L; Wolkon, Adam; Mutenda, Nicholus; DeVos, Josh; Zheng, Du-Ping; Wagar, Nick; Prybylski, Dimitri; Yang, Chunfu; et al.
Abstract: Background: Continued use of standardized, first-line ART containing NNRTIs and NRTIs may contribute to ongoing emergence of HIV drug resistance (HIVDR) in Namibia. Methods: A nationally representative cross-sectional survey was conducted during 2015–16 to estimate the prevalence of significant pretreatment HIV drug resistance (PDR) and viral load (VL) suppression rates 6–12 months after initiating standardized first-line ART. Consenting adult patients (≥18 years) initiating ART were interviewed about prior antiretroviral drug (ARV) exposure and underwent resistance testing using dried blood spot samples. PDR was defined as mutations causing low-, intermediate- and high-level resistance to ARVs according to the 2014 WHO Surveillance of HIV Drug Resistance in Adults Initiating ART. The prevalence of PDR was described by patient characteristics, ARV exposure and VL results. Results were weighted to be nationally representative. Results: Successful genotyping was performed for 381 specimens; 144 (36.6%) specimens demonstrated HIVDR, of which 54 (12.7%) demonstrated PDR. Resistance to NNRTIs was most prevalent (11.9%). PDR was higher in patients with previous ARV exposure compared with no exposure (30.5% versus 9.6%) (prevalence ratio = 3.17; P < 0.01). Conclusions: This survey demonstrated overall PDR at >10% among adults initiating ART in Namibia. Patients with prior ARV exposure had higher rates of PDR. Introducing a non-NNRTI-based regimen for first-line ART should be considered to maximize benefit of ART and minimize the emergence of HIVDR.